1997
DOI: 10.1021/om961011x
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Methyl(hydrido)platinum(IV) Complexes

Abstract: The new complex [PtMe2(BPMA)], 1, BPMA = bis(2-pyridylmethyl)amine, is shown to contain bidentate BPMA with one of the pyridyl groups not coordinated to platinum. Complex 1 reacts with HX (X = Cl, BF4) at room temperature to yield [PtHMe2(BPMA)][X], which may exist in two isomeric forms, each containing tridentate BPMA. The major initial product 2 has the hydride trans to a pyridyl group, but this equilibrates with isomer 3 in which the hydride is trans to an amine. The cationic methyl(hydrido)platinum(IV) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 36 publications
7
82
0
2
Order By: Relevance
“…Furthermore, in deuterated acidic media, multiple H/ D exchange into the alkyl positions is observed prior to elimination of the alkane for certain classes of these alkyl hydride complexes. [56,60,61,66] The results from these studies support the mechanism shown in Scheme 5 for the protonolysis of alkylplatinum(ii) complexes: a) chloride-or solventmediated protonation of Pt II (F) to generate an alkyl(hydrido)platinum(iv) intermediate (G); b) dissociation of the solvent molecule or chloride to generate a cationic, fivecoordinate platinum(iv) species (H); c) reductive C ± H Scheme 5. Proposed mechanism for the protonolysis of alkylplatinum(ii) complexes, the microscopic reverse of C ± H activation by Pt 2À is present in the reaction mixture, ethyl chloride is generated.…”
Section: Electrophilic Activation Of Alkanes By Platinum(i II I)supporting
confidence: 67%
“…Furthermore, in deuterated acidic media, multiple H/ D exchange into the alkyl positions is observed prior to elimination of the alkane for certain classes of these alkyl hydride complexes. [56,60,61,66] The results from these studies support the mechanism shown in Scheme 5 for the protonolysis of alkylplatinum(ii) complexes: a) chloride-or solventmediated protonation of Pt II (F) to generate an alkyl(hydrido)platinum(iv) intermediate (G); b) dissociation of the solvent molecule or chloride to generate a cationic, fivecoordinate platinum(iv) species (H); c) reductive C ± H Scheme 5. Proposed mechanism for the protonolysis of alkylplatinum(ii) complexes, the microscopic reverse of C ± H activation by Pt 2À is present in the reaction mixture, ethyl chloride is generated.…”
Section: Electrophilic Activation Of Alkanes By Platinum(i II I)supporting
confidence: 67%
“…66,67 Other studies also observed hydridoalkylplatinum(IV) species during low-temperature protonation. [68][69][70][71][72] This lead to the assumption of an oxidative addition mechanism of an alkane to the metal, presumably from a 75 With bulky substituent in the ortho position of the diimine ligand, η 2 -benzene coordination appeared rate limiting while in the absence of ortho substituent, the C-H cleavage became the rate determining step. This was explained by steric destabilisation of both the intermediate π-benzene complex and the transition state by the ortho methyl group.…”
Section: Methodsmentioning
confidence: 99%
“…Its transition metal complexes display a rich chemistry and have a considerable importance in homogeneous catalysis because they often represent key intermediates in C-C coupling reactions [22]. Whereas the g 3 bonding mode is the most general for this ligand, some g 1 -allyl complexes have been isolated, mainly with platinum [23], rhodium [24], iridium [25], or early transition metals [26]. This g 1 -allyl type of bonding to a transition metal affects the stereochemistry of reactions proceeding via allyl intermediates and it is well known in Pd-allyl chemistry that a g 3 -g 1 -g 3 dynamic behaviour may be operative which can be either detrimental to, or required for enantioselection [22].…”
Section: -Allyl Complexesmentioning
confidence: 99%